An Analysis of Students' Motivation for Using Online Platforms in English Learning - Harum Natasha; Miftahul Jannah (Journal of English and Arabic Language Teaching, 2024)
This research investigated students' motivation to learn English by a media of online platforms. The purpose is to find out the type of motivation they have, and the kinds of motivation in learning that they experienced. In the class of grade 7th  at Islamic Junior High School Al-Fityah, Pekanbaru, Indonesia, the teaching and learning process used 3 online platforms. They are Kahoot, Quizizz, and Google Form. The method of the research was a descriptive qualitative method. The researchers used observation and interview as the instruments. The observation data was got from the samples of 2 classes (@25 people). The result of the observation showed that the samples had intrinsic motivation higher than extrinsic motivation. Meanwhile, From the interview, it showed that students' motivation to use online platforms to learn English promoted every part of ARCS that are Attention, Relevance, Confidence, and Satisfaction.